Requirements for OS security mechanisms within the class of use - Бичков, Олексій Сергійович; Шестак, Яніна Володимирівна (Київський національний університет імені Тараса Шевченка, 2020)
One of the components of modern information systems is general-purpose computer equipment on which specialized software is installed or on which specialized software is working. This computer equipment requires a general-purpose operating system. To protect the information system it is necessary to protect all its links, including the operating system. In particular, in case of client-server technologies it is necessary to pay attention both to protection of server component and to protection of a client component. Protection of an operating system demands understanding, within what limits of what information system the OS will work, what working conditions and restrictions are imposed on the protected environment, what threats to the protected environment is required, what mechanisms is it possible to provide with protection of the environment necessary to us and what "price" of their application or nonapplication and other will be. Therefore, software safety should rely on a policy of safety of an operating system, expanding and specifying it and as much as possible. It is necessary to rely on safety mechanisms which are provided by an operating system or information system at software working out. This is necessary for unification and simplification of system of safety, simplification of its service, at the expense of reduction of quantity of the mechanisms created for the decision of the same problem. It is also necessary to apply typical and well-known components and standards, to avoid components with the closed source code as much as possible, or components which do not support, or incorrectly support typical standards. Obviously, incorrect protection of the operating system can lead to the failure of the security system as a whole, because the operation of specialized software and work with peripherals is under the control of the operating system. In article in detail offers concerning requirements to mechanisms of protection of operating systems are considered. These requirements are focused not on universal requirements, and consider various variants of use of computer devices.

Одним з компонент сучасних інформаційних систем є комп’ютерна техніка загального призначення, на якій встановлене спеціалізоване програмне забезпечення, або з якої ведуть роботу із спеціалізованим програмним забезпеченням. Для роботи цієї комп’ютерної техніки необхідна операційна система загального призначення. Для захисту інформаційної системи необхідно захистити усі її ланки, в тому числі операційну систему. Зокрема, у випадку клієнт-серверних технологій слід приділити увагу як захисту серверної компоненти, так і захисту клієнтської компоненти. Захист операційної системи вимагає розуміння, в рамках якої інформаційної системи буде працювати ОС, які умови роботи та обмеження накладаються на захищене середовище, захист від яких загроз буде потрібен захищеному середовищу, якими механізмами можна забезпечити потрібну нам захищеність середовища та яка буде «ціна» їх застосування чи незастосування та інше. Тому безпека програмного забезпечення має спиратися на політику безпеки операційної системи, розширюючи та уточнюючи її та наскільки це є можливим. При розробці програмного забезпечення слід спиратися на механізми безпеки, які передбачені операційною системою або інформаційної системою. Це потрібно для уніфікації та спрощення системи безпеки, полегшення її обслуговування, за рахунок зменшення кількості механізмів, які створені для розв’язання однієї і тієї ж задачі. Також слід застосовувати типові та загальновідомі компоненти та стандарти, по можливості уникати компонентів з закритим вихідним кодом, або компонентів, які не підтримують, або некоректно підтримують типові стандарти. Очевидно, що неправильний захист операційної системи може привести до провалу системи безпеки в цілому, бо робота спеціалізованого програмного забезпечення та робота з периферійними пристроями відбувається саме під контролем операційної системи. В статті детально розглянуті пропозиції щодо вимог до механізмів захисту операційних систем. Ці вимоги орієнтовані не на універсальні потреби, а враховують різні варіанти використання комп’ютерних пристроїв.
Вимоги до механізмів захищеності ОС в рамках класу використання
Keywords: security; operating system; classification; requirements; level; захищеність; операційна система; класифікація; вимоги; рівень